The relationship between faculty characteristics and the use of norm- and criteria-based grading - John Robst; Jennifer Van Gilder (Cogent Economics & Finance, 2016)
Norm-based grading has been associated with a reduction in student incentives to learn. Thus, it is important to understand faculty incentives for using norm-based grading. This paper used two waves of the National Study of Postsecondary Faculty to examine faculty characteristics related to the use of norm-based grading. Results suggest that norm-based grading is more likely when faculty and departments are more research oriented. Faculty who are at lower rank, male, younger, in science and social science departments are more likely to use norm-based grading, while faculty who feel that teaching should be the primary promotion criterion use criteria-based grading.
Keywords: 330; grading standards; value of time; student effort